FREQUENCY OF VALPROATE-INDUCED THROMBOCYTOPENIA IN CHILDREN WITH EPILEPSY IN PAEDIATRIC ICU - DR MEHBOOB AHMED, BRIG. DR. MUNIR AKMAL LODHI, DR AWAIS TAHIR, DR MUHAMMAD IBRAR KHAN, DR KAMRAN ULLAH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Valproic acid (VPA) is common in paediatric practice as a first-line antiepileptic medication and has been shown in numerous studies to have thrombocytopenia as one of the most clinically significant adverse effects. Objective: To determine the frequency of valproate-induced thrombocytopenia in children with epilepsy admitted to the PICU. Study Design and Setting: A cross-sectional descriptive study conducted in the Paediatric Intensive Care Unit of Fauji Foundation Hospital, Rawalpindi from June 2025 to September 2025. Methods: Consecutive sampling was used to recruit 62 children aged 1-12 years who were on intravenous valproate at least one day. The baseline and daily platelet counts were taken. Dose, duration and route of administration of valproate in data were gathered. Chi-square tests, independent samples t-tests, and repeated-measures ANOVA were used to analyse associations between variables of exposure and thrombocytopenia. The p-value of less than 0.05 was viewed as statistically significant. Results: Thrombocytopenia was present in 30.6 percent of the group. Kids who had thrombocytopenia got much more mean daily doses of VPA than those who did not (32.1 ± 6.8 vs. 26.5 ± 7.4 mg/kg/day; p = 0.003). Thrombocytopenia was also related to the long duration of treatment (5.1 ± 1.9 vs. 3.7 ± 1.6 days; p = 0.003). The majority of the cases were developed during the period of 3-7 days of therapy. There was no pronounced correlation between the route of administration and thrombocytopenia (p = 0.71). The repeated-measures ANOVA was found to be significant with respect to a downward shifting trend in platelets over time in the affected children (p = 0.01). Conclusion: Valproic acid is linked to high risk of thrombocytopenia in PICU-hospitalized children especially when dosages are increased and when treatment is prolonged. The significance of the daily haematologic surveillance within the initial week of the treatment is emphasized by the early platelet trend deterioration.